THE ROLE AND SIGNIFICANCE OF THE SCIENTIFIC AND CREATIVE HERITAGE OF ABU RAYHAN BERUNI IN EDUCATING STUDENTS IN THE SPIRIT OF PATRIOTISM (Modern American Journal of Biological and Environmental Sciences, 2025)
This article examines the role and importance of the scientific and creative heritage of Abu Rayhan Beruni in the development of the modern system of education and upbringing, particularly in educating the younger generation, including students, in the spirit of patriotism within the education system of our country. It also highlights that reforms carried out in the economic, social, spiritual, and educational spheres have been elevated to the level of state policy.